2016
DOI: 10.1111/aos.13154
|View full text |Cite
|
Sign up to set email alerts
|

Human bone marrow mesenchymal stem cells for retinal vascular injury

Abstract: Intravitreally implanted human BMSCs were associated with a reduced retinal neovascularization in the oxygen-induced retinopathy model and with a potentially cell preserving effect in the retinal ischaemia-reperfusion model. Intravitreal BMSCs may be of potential interest for the therapy of retinal vascular disorders.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 34 publications
0
15
0
Order By: Relevance
“…Intravitreal administration of MSCs has demonstrated improvement in outcomes in several animal models of retinal injury and dysfunction (100104); however, the safety of intravitreal injection of MSCs in humans is still an area of clinical concern (105).…”
Section: Routes Of Therapeutic Cell Deliverymentioning
confidence: 99%
“…Intravitreal administration of MSCs has demonstrated improvement in outcomes in several animal models of retinal injury and dysfunction (100104); however, the safety of intravitreal injection of MSCs in humans is still an area of clinical concern (105).…”
Section: Routes Of Therapeutic Cell Deliverymentioning
confidence: 99%
“…Several studies have suggested that the successful reconstruction of damaged ocular tissues by MSCs was more dependent on the release of paracrine anti-inflammatory and anti-angiogenic factors than differentiation into ocular cells [120][121][122]. Thus, when human BMSCs were intravitreally implanted in an oxygen induced retinopathy mouse model, it significantly reduced retinal neovascularization [123]. When engineered to secrete therapeutic dose of anti-angiogenic factor PEDF, BMSCs were recruited to CNV lesions and inhibited neo-angiogenesis in vivo [124].…”
Section: Mscs Modulate Angiogenesismentioning
confidence: 99%
“…In this study, we found that the BMSC remodeled the vascular network and reduced the avascular areas and neovascularization. Similar effects were observed in multiple animal models of retinal neovascularization by using human BMSC [11]. However, we specifically examined the role of BMSC and compared with Conbercept, which is an important anti-VEGF drug that is clinically used for the treatment of ocular neovascularization.…”
Section: Retinal Histology and Apoptosis Assaymentioning
confidence: 71%